Co-pyrolysis of sugarcane bagasse and polystyrene with ex-situ catalytic bed of metal oxides/HZSM-5 with focus on liquid yield. (October 2019) - Iftikhar, Hera; Zeeshan, Muhammad; Iqbal, Saeed; Muneer, Bushra; Razzaq, Madiha
Highlights: Dual pore size acidic/basic catalyst for chemical selectivity was studied. Liquid yield decreased with increasing acidic HZSM-5 in the catalyst. HZSM-5:MgO produced better physicochemical oil characteristics than HZSM-5:CaO. Abstract: Catalytic co-pyrolysis of sugarcane bagasse (SCB) and polystyrene (PS) was conducted in a fixed bed reactor over microporous HZSM-5, mesoporous metal oxides (MgO, CaO) and their blends to examine the effect on pyrolytic liquid yields and quality. Though the catalyst addition decreased the liquid yield, improvement in mono-aromatic hydrocarbon yield with the least content of oxygenates was achieved in the catalytic trials. Results revealed that HZSM-5 showed maximum conversion efficiency of acids, furans and phenols acting as hydrocarbon source for aromatic production. Basic MgO, with acidic HZSM-5, was found to conduce better catalytic performance yielding improved oil quality compared to HZSM-5:CaO catalyst. Mass ratio of 1:3 HZSM-5:MgO exhibited most eminent synergistic effect with maximum (56.8 wt%) mono-aromatic hydrocarbon (MAH) yield and lowest (20.8 wt%) poly-aromatic hydrocarbon (PAH) content. Additionally, increased calorific value and density upgradation comparable to standard diesel fuel quality were observed in the presence of dual catalyst layout.